Pharmacological correction of plasma redox potential and endothelial dysfunction in ischemic heart failure - O. P. Donetskaya; V. A. Tulupova; N. V. Shuldeshova; M. M. Fedorova (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To study the role of plasma redox potential reduction in the development of endothelial dysfunction (ED) among patients with chronic heart failure (CHF) and to investigate the potential of its pharmacological correction. Material and methods. This randomised cohort study included 73 patients with CHF, due to coronary heart disease (CHD) and arterial hypertension. Mean age of the participants was 59,2±5,9 years. Functional Class (FC) I CHF was registered in 9 patients, FC II CHF in 21, FC III CHF in 23, and FC IV CHF in 11. After the baseline examination, all participants were randomised into two groups. The main group (MG) received standard therapy plus adenocin (2 ampoules in 70 ml 5% glucose, intravenously) for 10 days. Results. For the first time, the dynamics of redox potential and total pyridine nucleotide levels was assessed in relation to the FC of ischemic CHF. Redox potential reduction preceded the changes in the total pyridine nucleotide levels. In contrast to standard therapy, adenocin increased plasma redox potential and endothelial growth factor levels, while reducing endothelin-1 concentrations and NADPH oxidase activity. Conclusion. Combination therapy with adenocin – a unique medication of reduced NAD form, cardiac glycoside, and inosine, in contrast to standard treatment, significantly increased cellular redox potential in CHF, which could play an important role in angiogenesis stimulation and reverse endothelial remodelling.